2018 Vegetable Production Handbook Chapter 13: Pepper Production - Monica Ozores-Hampton; Nathan S. Boyd; Eugene J. McAvoy; Christian F. Miller; Johan Desaeger; Joseph W. Noling; Gary E. Vallad (EDIS, 2018)
This 33-page fact sheet is chapter 13 of the 2018 Vegetable Production Handbook. Written by Monica Ozores-Hampton, Nathan S. Boyd, Eugene J. McAvoy, Christian F. Miller, Johan Desaeger, Joseph W. Noling, and Gary E. Vallad, and published by Horticultural Sciences Department, 2018.